THE EFFECT OF INCOME, FINANCIAL LITERACY, AND SELF-CONTROL ON CONSUMPTIVE BEHAVIOR IN K-POP FANS IN KARAWANG - Lisa Ara Ghea Sagala; Dedi Mulyadi; Santi Pertiwi Hari Sandi (SEAN Institute, 2023)
This study aims to determine and analyze the influence of income variables, financial literacy, and self-control on consumptive behavior in K-Pop Karawang fans, as well as find out the most influential factors on consumptive behavior. The study used a descriptive verifiable method with a quantitative approach, with sampling techniques, namely purposive sampling and using the Lemeshow formula. This research was conducted by survey method using a Likert scale questionnaire distributed to 100 respondents of K-Pop fans in Karawang. Data analysis techniques use path analysis with partial and simultaneous hypothesis tests. The results showed that self-control had a positive and significant effect on partial consumptive behavior, while income and financial literacy did not have a positive and significant effect on partial consumptive behavior. Simultaneously, the variables of income, financial literacy, and self-control have a positive and significant influence on consumptive behavior.